Innowacje edukacyjne - wczoraj, dziś i jutro - Ratajczak, Krzysztof; Konstańczak, Marta; Sobierajska, Alicja; Kontowski, Daniel; Smoleń, Rafał; Czujko, Ewelina; Oleksy-Zborowska, Magdalena; Rodak, Olga; Drzymała, Edyta (My University, 2014)
The book consists articles focuses on the problem of innovation, both, in theory, and practise of education.
Keywords: edukacja; innowacje edukacyjne; historia edukacji